Language Skills for Higher Education in Tanzania - Rugemalira, Josephat (JULACE: Journal of the University of Namibia Language Centre, 2018)
This paper argues that there are two radical policy options available to the higher education establishment in Tanzania with regard to the issue of the language medium of instruction. The first option requires the establishment of a strict filtering mechanism in order to exclude all applicants who do not possess the English language skills required in an English medium university. The second option seeks to develop a bilingual language policy for higher education. This would allow partial use of Kiswahili in the system e.g. in lectures, seminar discussions and examinations, even while most literature has to be accessed in English. The paper presents an account of the conditions that call for such a radical departure from current practice, showing that the much utilized ‘University of Dar es Salaam Model’ of Communications Skills courses has not had the expected impact.